Mobile-Based Learning Application Concerning Religious Moderation at MTsN 2 Medan Using the Waterfall Method - Pasaribu, Mahadir; alda, Muhamad (ZERO: Jurnal Sains, Matematika dan Terapan, 2023)
Religious moderation is a religious perspective by understanding and practicing religious teachings in a balanced or non-extreme way. Currently, learning about religious moderation is only carried out at school, which is explained by a teacher. Limited insight into religious moderation is one of the factors why students lack empathy towards religious communities. Therefore, a mobile- based learning application is needed that can be the right solution to bring learning about religious moderation into the hands of students, facilitating access and learning outside the classroom to create a young generation that understands differences, and understands that religious diversity is something that normal in society. The tools used to design this system are UML (Unified Modeling Language), which consists of Use Case Diagrams, Sequence Diagrams and Class Diagrams. The application system was built using Android Studio as the programming language and Firebase as the database. It is hoped that this application can be an effective means of increasing students' understanding of religious moderation so as to make a positive contribution in creating a young generation that respects differences, and becomes agents of peace in a society with diverse religions and beliefs.